Kewajiban Negara Dalam Melindungi Hak Lingkungan Baik dan Sehat Masyarakat Adat Awyu Berdasarkan Hak Asasi Manusia - Dimas Pangastuti; Erna Dyah Kusumawati (Program Pascasarjana Fakultas Hukum Universitas Sebelas Maret Surakarta, 2024)
AbstractIndigenouspeoples are communities that live side by side with forests and tend to apply sustainable principles for the environment for generations. Indigenous peoples are at the forefront of the fight against climate disasters. The irony is the lack of access to education and understanding is often used by certain parties to reap benefits in an unfair way. In fact, indigenous peoples as part of Indonesian citizens also have the right to benefit from the earth, water and all natural resources in this country as stated in Article 33 Paragraph 3 of the 1945 Constitution of The Republic Indonesia, and their rights are recognized by the state as stated in Article 18 B of the 1945 Constitution of the Republic Indonesia. On that basis, this article will analyze how the state’s obligation to protect the right to a good and healthy environment for the Awyu Tribe based on Human Rights. This Type of research is normative, prespective in nature with a statutory approach and uses secondary data in the form of primary legal materials and secondary legal materials. This article aims to find the essence of the state’s obligation to protect the right to a good and healthy environment for indigenous peoples, especially the Awyu Tribe.